Borders across Healthcare Moral Economies of Healthcare and Migration in Europe - Sahraoui, Nina (Berghahn Books, 2020)
Examining which actors determine undocumented migrants' access to healthcare on the ground, this volume looks at what happens in the daily interactions between administrative personnel, healthcare professionals and migrant patients in healthcare institutions across Europe. Borders across Healthcare explores contemporary moral economies of the healthcare-migration nexus. The volume documents the many ways in which borders come to disrupt healthcare settings and illuminates how judgements of a health-related deservingness become increasingly important, producing hierarchies that undermine a universal right to healthcare.